Ukrainian issue in diplomatic activity of the Ukrainian People's Republic and Western Ukrainian People's Republic in the Serb, Croats and Slovenes Kingdom - Sagan, Galyna (Skhid : analitychno-informat͡s︡iĭnyĭ z͡h︡urnal, 2025)
The article examines the formation and activities of the diplomatic service of the Ukrainian People's Republic (UPR) in the Kingdom of Serbs, Croats, and Slovenes (SCS) in the 1920s. The research is based on newly discovered archival documents that have allowed for important conclusions regarding the UPR's international activities. The author argues that despite the pro-Russian sentiment in official Serbian circles and the lack of official recognition of the UPR, Ukrainian diplomats, particularly H. Myketei, S. Lukianovych, and M. Slavinsky, achieved significant success. They conducted active outreach, spreading the "Ukrainian idea" and providing objective information to the Yugoslav public about the state of the Ukrainian nation, its history, and its aspirations for independence. The diplomats also cared for the Ukrainian community in the Kingdom of SCS, specifically by uniting interned servicemen and providing them with material and moral support. They established strong ties with Ukrainians who had immigrated to Yugoslavia earlier. A key factor was the Ukrainian diplomats' use of an unconventional situation, namely the willingness of Croatian, Slovenian, and Macedonian representatives to cooperate. M. Slavinsky expanded the activities of the UPR missions into non-Serbian regions, which helped to foster a positive perception of Ukrainians as a nation striving to create its own independent state. Ultimately, however, the active diplomatic work of the UPR and WUPR missions in the Kingdom of SCS was hindered by the Bolshevik regime that was established in Ukraine.